Legal Review of the Implementation of Public Information Openness Based on Laws and Internal Regulations at PT Pelabuhan Indonesia (Persero) Regional 1 - Joyce Vania Sarumaha; Martono Anggusti; Jinner Sidauruk (Journal of Law, Politic and Humanities, 2025)
Public information disclosure is a key factor in building public trust and establishing good governance to ensure transparent and accountable management. This study aims to analyze the implementation of public information disclosure at PT Pelindo Regional 1 in accordance with Law No. 14 of 2008 on Public Information Disclosure, applicable board regulations, and established public information service guidelines. This research employs a normative legal method, focusing on analyzing relevant legislation, complemented by an empirical approach to collect and examine data related to the implementation of public information disclosure at PT Pelindo Regional 1. Data collection techniques include interviews with relevant stakeholders within the company to gain insights into the practical implementation of public information disclosure. The findings reveal that although PT Pelindo Regional 1 has made efforts to fulfill its public information disclosure obligations, challenges remain in delivering information to the public, particularly in terms of public awareness regarding their rights to access information. The study also identifies the categories of information disclosed to the public and information exempted from public disclosure, highlighting the limitations imposed on public access to certain information. Based on these findings, the study provides recommendations to enhance the effectiveness of public information disclosure at PT Pelindo, including increasing public awareness campaigns and strengthening existing public information systems.